AGRICULTURAL APP - TIBILE POONAM; KIROLKAR POOJA; WASKAR SARITA (International Journal of Innovations in Engineering Research and Technology, 2021)
In current agricultural scenario, the main aim of agricultural experts to provide proper up-to-date information to the farmers so that they can efficiently utilize the given information to improve their agricultural practices and thereby increase the production. The huge amount of agricultural data is generated from the different sources whichhave to be handled efficiently. By the use of ICT we can handle this data generated from different sources and can build knowledge based system to provide experts advices to the farmers.